(untitled) (Per Musi, 2021)
This paper presents a review in the areas of cognitive musicology, neuroscience and music therapy in the field of music and attention. The text is divided into three sections that group a review of related studies: (a) Theoretical foundations of attention and music; (b) Neuroscientific evidence on attention and music; (c) Therapeutic applications of music in attention. Studies of cognitive musicology show that perceptual groupings and expectations are determining factors for the recruitment of the various dimensions of attention. Neuroimaging exams, neuropsychological tests and studies on rhythmic synchronicity add neuroscientific evidence about the strong relationship between music and attention. The evidence reported in this study demonstrates that music can be used in a therapeutic context with beneficial effects for people with impaired attention or as a resource to distract attention from painful sensations or stressful situations.